Measuring spatial scoring effectiveness in women's basketball at the 2016 Olympic Games. (2nd November 2018) - Hobbs, Wade; Gorman, Adam D.; Morgan, Stuart; Mooney, Mitchell; Freeston, Jonathan
ABSTRACT: Basketball strategy is often focused on how to use space on the court. However, very little research has investigated performance from a spatial perspective beyond the now ubiquitous shooting heat maps. The aim of this study was to quantify how effectively teams move the ball across the basketball court and identify the most commonly occurring sequences of ball movement in international women's basketball. The results of the spatial analysis characterised trends in team play from the women's 2016 Olympic basketball competition and demonstrated that overall, the right-hand side under the basket and the top-right 3-point area were the most-effective areas on the court. In general terms, the right-hand side of the court was more effective than the left, and the middle of the court was more effective than the wings. Of the teams included in the study, the United States of America demonstrated the greatest overall effectiveness. Finally, the most commonly occurring ball movement sequences were identified with five of the seven teams demonstrating the same pattern. The quantification of spatial effectiveness in the current study provides insight into the specific tendencies of different teams and the areas that lead to the most effective outcomes. Coaches can apply this information to devise game plans aimed at counteracting the specific tendencies of opposing teams.